Human computer interaction research in Web design and evaluation - Zaphiris, Panayiotis; Kurniawan, Sri Hastuti (My University, 2007)
Human Computer Interaction Research in Web Design and Evaluation presents real research from academics and industry experts, covering various aspects of human computer interaction (HCI) web design from theories to evaluation. It highlights the use of methods from HCI area in web design and how these methods could be used in a practical sense. Human Computer Interaction Research in Web Design and Evaluation is a comprehensive book on HCI and Web design that focuses on various areas of research including theories, analysis, design and evaluation. This book not only features the human aspect of web design, but also highlights the social and cultural issues in designing for wider audience.